Tradition or Modernization? The Dilemma of Chinese Indigenous Communities. Issue 5 (4th May 2023) - Li, Qiuxi; Subica, Andrew; Kendra, James; Ali, Saleem H.
ABSTRACT: In the indigenous communities in China's Guizhou Province, people are struggling to balance tradition with modernisation. As fires have long plagued these villages, post-disaster reconstruction has intensified the tradition/modernity tension and left people with a complex dilemma: should traditional wooden houses be restored, or should one, instead, pursue a safer and modern dwelling in concrete houses? Through the lens of housing reconstruction, this paper aims to address this contradiction between the social benefits of heritage preservation and the indigenous rights for development in the context of disaster risk and modernisation in Guizhou Province. Analysing 134 surveys and 29 interviews collected via ethnographic fieldwork, this study's findings reveal two core themes. First, the presence of a prevailing preference among indigenous Chinese for modernity, which also challenged the conventional wisdom that everyone endorses heritage preservation. Second, a social expectation among indigenous Chinese to be faithful to their cultural traditions and to resist development; which could be perceived as a continuation of the historical injustices and exploitations perpetrated against them. Overall, study findings call for a more inclusive and comprehensive discourse of indigenous preservation and development.